Efforts to Imporove Students Reading Comprehension Skills During the Face to Face Learning Period are Limited Through the Speed Reading Method in Elementari School: Upaya Meningkatkan Kemampuan Membaca Pemahaman Peserta Didik Pada Masa Pembelajaran Tatap Muka Secara Terbatas Melalui Metode Speed Reading di Sekolah Dasar - Titah Azariska; Vevy Liansari (Academia Open, 2022)
This study aimed to investigate the influence of the speed reading method on the reading comprehension ability of fourth-grade students in an elementary school setting. A quantitative experimental approach was employed, utilizing a One Group Pretest-Posttest research design. The sample consisted of 21 students from SDN Kalitengah II. Pre-test and post-test data were collected through descriptive question sheets. Prior to implementing the speed reading method, students' learning outcomes were predominantly categorized as very low (80.96%) and low (19.04%). However, after implementing the speed reading method, the distribution significantly improved, with only 5.55% classified as very low, and a majority achieving high (77.78%) and very high (16.67%) scores. Statistical analysis using the t-test yielded a tCount of 4.35, surpassing the tTable value of 1.725, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). Thus, the findings indicate that the speed reading method positively impacts students' reading ability. These results have important implications for enhancing reading comprehension in elementary education settings. Highlights: Speed reading improves reading comprehension: This study demonstrates the positive impact of the speed reading method on enhancing reading comprehension among elementary students. Quantitative experimental approach: The study utilized a rigorous quantitative experimental design to examine the effects of speed reading on students' reading abilities. Significant improvement in learning outcomes: The findings revealed a significant improvement in students' learning outcomes, with a majority achieving high and very high scores after implementing the speed reading method. Keywords: speed reading, elementary students, reading comprehension, quantitative experimental study, learning outcomes.